Paradigma Air Guraka Saat Pandemi Covid-19 dan New Normal di Kota Ternate sebagai Peluang Usaha - Rima Melati; Nur Syafira Rahmadani; Suryati Tjokrodiningrat; Febrianti Nyong; Subhan Baswan (xxxx-xxxx, 2020)
Melati R, Rahmadani NS, Tjokrodiningrat S, Nyong F, Baswan S. The paradigm of guraka water during the covid-19 pandemic and new normal in Ternate city as business opportunities. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang  20 Oktober 2020. pp. xx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The graph of infected people in Indonesia is increasing every day until the fourth month after the corona virus outbreak. Various preventive efforts have been recommended as changing healthy lifestyles by maintaining the body's immune system. The aim of the research is to get information about the paradigm of guraka water by the community during the pandemic, which is viewed from the social, health and business opportunities of farmers. The method is a survey and interview with purposive sampling techniques and literature studies. Data analysis uses SWOT analysis. The results showed that the habit of people consuming guraka water with the aim of promoting social values while increasing endurance becomes an opportunity for farmers to work on ginger cultivation. The social value of guraka water is the social and social order, a symbol of appreciation for guests and acknowledgment. The health aspect study explains that ginger has antioxidant compounds and vitamin C which is thought to form a better immune system. The rise of the community consumes guraka water, which means the demand for local ginger continues to increase and this opens up a business opportunity for ginger cultivation to maintain ginger stock in the market to meet the demand for guraka water sellers and small entrepreneurs in the city of Ternate and surrounding areas. Guraka water is local knowledge and supported by promotions from various parties so that it can provide added value to the people of Ternate City and more importantly can maintain the body’s immune.